2004
DOI: 10.1038/sj.emboj.7600340
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA control of PHABULOSA in leaf development: importance of pairing to the microRNA 5′ region

Abstract: MicroRNAs (miRNAs) are B22-nucleotide noncoding RNAs that can regulate gene expression by directing mRNA degradation or inhibiting productive translation. Dominant mutations in PHABULOSA (PHB) and PHAVOLUTA (PHV) map to a miR165/166 complementary site and impair miRNA-guided cleavage of these mRNAs in vitro. Here, we confirm that disrupted miRNA pairing, not changes in PHB protein sequence, causes the developmental defects in phb-d mutants. In planta, disrupting miRNA pairing near the center of the miRNA compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
476
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 632 publications
(514 citation statements)
references
References 68 publications
23
476
1
4
Order By: Relevance
“…miR165/6 (21 nucleotides) family members play important roles in plant development by targeting type III HD-Zip genes REVOLUTA, PHABULOSA, and PHAVOLUTA to regulate leaf polarity and stem cell identity (Mallory et al, 2004;Williams et al, 2005). In hen1 mutants, we observed that miR166 is first truncated to ;17 nucleotides without any tailing and then is uridylated to ;21 nucleotides, its original length ( Figure 1B).…”
Section: Mirnas Are Differentially Truncated and Uridylated In Hen1 Mmentioning
confidence: 87%
“…miR165/6 (21 nucleotides) family members play important roles in plant development by targeting type III HD-Zip genes REVOLUTA, PHABULOSA, and PHAVOLUTA to regulate leaf polarity and stem cell identity (Mallory et al, 2004;Williams et al, 2005). In hen1 mutants, we observed that miR166 is first truncated to ;17 nucleotides without any tailing and then is uridylated to ;21 nucleotides, its original length ( Figure 1B).…”
Section: Mirnas Are Differentially Truncated and Uridylated In Hen1 Mmentioning
confidence: 87%
“…7 positions (No. 1 being overrepresented by a U), are critical for target recognition (Doench and Sharp, 2004;Mallory et al, 2004;Brennecke et al, 2005;Krek et al, 2005;Lai et al, 2005;Lewis et al, 2005). Prediction of miRNAs by current computational methods or detection of miRNAs by Northern blot and microarray analyses cannot pinpoint the ends of miRNAs.…”
Section: Mirnas: the Modificationsmentioning
confidence: 99%
“…Perfect complimentarity at this 5′ region of miRNAs has been previously shown to be critical for miRNA function (Mallory et al 2004b). If NbAP2 also has such a mismatch to Arabidopsis miR172, it seems possible that Arabidopsis miR172 may not be having a repressive effect on NbAP2 but instead could be sequestering NbAP2 mRNA from being regulated by NbmiR172 to result in increased NbAP2 activity.…”
Section: Floral Homeotic Transformations and Early Flowering In N Bementioning
confidence: 99%